LANGKAH PREVENTIF MENANGGULANGI PERUNDUNGAN VERBAL MELALUI BOOKLET PADA SISWA SMPN DI SURABAYA TIMUR - Prasetyo, Eli; Christanti, Dessi; Susilo, Dicky; Adhyatma, Made Dharmawan Rama (Jurnal Abdimas Musi Charitas, 2025)
Purpose : This community service activity aimed to address the issue of verbal bullying among junior high school students (SMPN) in East Surabaya. Although schools are expected to foster a safe and supportive climate, verbal bullying continues to emerge, particularly during students’ transition from elementary to junior high levels. Design/Methodology/Approach : The solution was implemented through a psychoeducational program involving the use of a booklet titled “Choose Words, Build Better Relationships”. The booklet contained material on verbal bullying and social skills development for adolescents. The program was delivered on December 6, 2024, involving 20 students and 8 guidance teachers from four SMPNs. Activities included a pre-test, group-based worksheet discussions guided by trained facilitators, a verbal bullying seminar, and a post-test. Evaluation was conducted using a 10-item questionnaire based on the booklet contents. Findings : The average pre-test score was 95.5, increasing slightly to 97 in the post-test. Although the quantitative improvement was modest, qualitative feedback indicated improved awareness of bullying, enhanced social problem-solving skills, and a more positive student mindset. Participants also showed enthusiasm in sharing knowledge with peers. Practical Implications : The booklet and psychoeducational method can be practically applied in other schools as a preventive measure to reduce verbal bullying. Teachers and peer leaders can replicate the method to cultivate a positive school environment and encourage anti-bullying behavior. Originality/Value : This project introduced a structured and replicable approach to bullying prevention that emphasizes student reflection and peer-based knowledge dissemination. The integration of the Stop-Think-Do method also adds value by equipping students with actionable steps to address interpersonal conflict.